AI: An Active and Innovative Tool for Artistic Creation - Charis Avlonitou; Eirini Papadaki (Arts)
This article aims to critically examine AI as both an active and innovative tool in artistic creation, investigating its evolving role in shaping artistic practices, expanding creative possibilities, and redefining the boundaries of human–machine collaboration. It traces the historical, conceptual, and technological integration of generative AI in art, particularly in relation to Modernism’s challenge to traditional norms. It also examines the ethical, social, and philosophical implications of AI art, focusing on issues such as authorship, legitimacy, and AI’s role in the cultural landscape. Through the analysis of two representative works—Refik Anadol’s Unsupervised and Anna Ridler’s Mosaic Virus—one mainstream and the other critically engaging with AI art’s social impact, the study examines the balance between technical innovation and conceptual depth, emphasizing transparency, originality, and human-centered approaches. Employing an extended literature review across chapters, the discussion synthesizes diverse sources to critically engage with ongoing debates. Ultimately, the article advocates for human–AI collaboration, emphasizing responsible integration to enhance creativity without losing the human essence of art. It offers highly valuable insights into the current debates surrounding AI in art and effectively guides the integration of AI into future creative practices.